Simulation Based Education for Building Skills in the Management of Emotional Dysregulation and Self-Harm on Children and Adolescent Mental Health Inpatient Wards - Antonia Winney; Damir Rafi; Naomi Tomlinson; Sam Ter-Horst (BJPsych Open)
Aims: Professionals in Child and Adolescent Mental Health Services (CAMHS) inpatient settings frequently manage cases of heightened emotional dysregulation, self-harm, and risky behaviours. Successful management required specialised techniques and a deep understanding of both therapeutic interventions and legal frameworks.